Comparison of Modified Radical Mastectomy with Breast Conservative Therapy and Radiotherapy in Patients with Breast Cancer - D Moslemi, (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Breast cancer is the most common malignancy among females and is one of the most common causes of cancer mortality in females aged 40-44 years. There are different methods of surgical treatment for breast cancer. Modified radical mastectomy (MRM) and breast conservative therapy (BCT) and radiotherapy are two methods for treatment of this disease. The present study aimed to survey loco- regional recurrence rate, metastasis, disease free survival and overall survival between modified radical mastectomy (MRM) and breast conservative therapy (BCT). METHODS: This historical cohort study was done with using extracting recorded data of 300 patients. One hundred and 200 patients were treated by BCT and MRM, respectively. Patients were followed up by visit in hospital and survival determined by phone call. Local recurrence, metastatic rates and survival were measured and compared.FINDINGS: The mean age (SD) of patients was 46.96±12.03 years and 46.79±11.21 years in BCT and MRM groups, respectively. There was not any significant difference between two groups. After two year follow up, loco regional recurrence was 4% (4 patients) in BCT group and 3% (6 patients) in MRM group, but after five year follow up, it was 8% (8 patients) in BCT group and 6% (12 patients) in MRM group. After two year follow up, mortality rate was 10% (10 patients) in BCT group and 4% (8 patients) in MRM group that there was no significant difference between two groups. Also after five year follow up, it was 16% (16 patients) in BCT group and 24% (48) in MRM group that there was no significant difference between two groups. CONCLUSION: we can recommend BCT for patients with breast cancer without any concern about increase of local recurrence and survival rate. The patients are more satisfied with BCT because of keeping their beauty, less psychological problems and better quality of life.